(untitled) (Agricultural Engineering, 2020)
A revalorised Burzyński’s hypothesis was suggested for determination of effort of construction elements in thermally variable load conditions. Using the suggested hypothesis, surfaces of the beginning of plasticity for the heat resistant St12T steel were determined. Two numerical simulations of thermo-mechanical loads of the turbine vane made of St12T steel were performed. The result of analyses was determination of the effort states of a vane acc. to Huber-Mises- Hencky’s hypotheis and according to the suggested revalorised Burzyński’s hypothesis.